Assessment of phospholipid fatty acid profiles for discrimination of salmonids cultured in freshwater and seawater. (February 2021) - Han, Cui; Dong, Shuanglin; Li, Li; Gao, Qinfeng; Zhou, Yangen
Abstract: Phospholipid fatty acid (PLFA) profiles were studied for their potential to discriminate between freshwater-cultured and seawater-cultured salmonids. The effects of culture season and fish size on the PLFAs compositions in salmonids were investigated to assess their effects on the discrimination results. Totally 19 PLFAs of salmonids were determined via gas chromatography (GC). Among them, 12 PLFAs were significantly different between freshwater-cultured and seawater-cultured salmonids. But only four PLFAs in salmonids cultured in different seasons and two PLFAs in fish with different size were significantly different. The PLFAs, including 18:1n9, 24:1n9, 20:5n3, 20:3n6, ∑MUFA, and ∑n6PUFA, were selected via stepwise discriminant analysis (SDA) for further multivariate statistics analysis. Principal component analysis (PCA) and canonical discriminant analysis (CDA) visualized the differences of the PLFAs profiles in fish cultured in freshwater and seawater. The linear discrimination analysis (LDA) and random forest (RF) were used to create a discrimination model that can authenticate salmonids farmed in freshwater and seawater. An overall correct classification rate of 95.89%, a cross-validation rate of 93.15%, and a predictive classification rate of 100% were achieved by the LDA. The RF achieved an overall correct classification rate of 95.89%, a cross-validation rate of 95.89%, and a predictive classification rate of 100%. These results indicate that PLFAs profiles can be used to effectively distinguish samples cultured in freshwater and seawater while less affected by season and fish size. Therefore, PLFAs analysis is a promising method for the accurate identification of salmonids cultured in freshwater and seawater. Highlights: Phospholipid fatty acid could distinguish salmonid from different culture areas. Season was found to affect only several phospholipid fatty acids in salmonid. Only 18:0 and 22:1n9 in salmonid were different among different fish sizes. The discrimination accuracy was less affected by seasonality and fish size.